Design and first tests of the Gotthard-II readout ASIC for the European X-ray Free-Electron Laser. (29th April 2021) - Zhang, J.; Andrä, M.; Barten, R.; Bergamaschi, A.; Brückner, M.; Chiriotti-Alvarez, S.; Dinapoli, R.; Fröjdh, E.; Greiffenberg, D.; Kozlowski, P.; Kuster, M.; Lopez-Cuenca, C.; et al.
Abstract: Gotthard-II is a charge-integrating microstrip detector developed for experiments and diagnostics at free-electron lasers using hard X-rays of 5 keV–20 keV. Thanks to its excellent single photon sensitivity, large dynamic range as well as high frame rate of 4.5 MHz in burst mode, its potential scientific applications include X-ray absorption/emission spectroscopy, hard X-ray high resolution single-shot spectrometry (HiREX), beam diagnostics, as well as veto signal generation for pixel detectors. The Gotthard-II ASIC has been designed and fabricated using UMC-110 nm technology. The final ASIC design and performance in terms of noise, linearity, dynamic range, coupling between channels and speed will be discussed in the paper. In addition, a first measurement of an X-ray absorption spectrum of a standard copper sample has been done. The performance of the Gotthard-II in an experiment using energy dispersive X-rays has been demonstrated.